(untitled) (Journal of Geography and Environmental Management, 2017)
Heavy metals are a group of chemical elements with a significant atomic weight or density. Heavy metals and their compounds in high concentrations may cause adverse effects on the human body. They can accumulate in the tissues and cause disease. Heavy metals and their compounds migrate from one habitat to another. Migration of the heavy metal compounds takes place in the form of organo-mineral component.Now pollution of heavy metals is one of the most harmful environmental factors, they have a negative impact on the life of organisms. Toxic effects of heavy metals, phenols, petroleum, nitrates, pesticides equally. This endangers the existence of civilization. The lead and mercury havenot beneficial roles in biological processes. They are toxic metals. Presence of heavy metals in the human life always increases. This leads to an increase in genetic mutations, cancer, cardiovascular diseases and occupational diseases, poisoning, dermatitis, decreased immunity and other diseases. The article presents the results of monitoring the impact of different concentrations of heavy metal ions on the natural biological materials – chicken protein, women’s breast milk. It was found the dependence of the destruction of the protein from the metal concentration